Effect of preoperative biliary drainage on bacterial flora in bile of patients with periampullary cancer. Issue 2 (25th January 2017) - Scheufele, F.; Aichinger, L.; Jäger, C.; Demir, I. E.; Schorn, S.; Sargut, M.; Erkan, M.; Kleeff, J.; Friess, H.; Ceyhan, G. O.
Abstract: Background: Patients with obstructive jaundice due to periampullary tumours may undergo preoperative biliary drainage (PBD). The effect of PBD on the microbiome of the biliary system and on postoperative outcome remains unclear. Methods: A single‐centre retrospective study of patients with obstructive jaundice due to periampullary cancer, treated between July 2007 and July 2015, was undertaken. Intraoperative bile samples were obtained for microbiological analysis after transection of the common bile duct. Postoperative complications were registered. Results: Of 290 patients treated, intraoperative bile samples were present for 172 patients (59·3 per cent) who had PBD and 118 (40·7 per cent) who did not. Contamination of bile was increased significantly in patients who underwent stenting (97·1 per cent versus 18·6 per cent in those without stenting; P < 0·001). PBD resulted in a shift in the biliary microbiome from Escherichia coli in non‐stented patients (45 per cent versus 19·2 per cent in stented patients; P = 0·009) towards increased contamination with Enterococcus faecalis (9 versus 37·7 per cent respectively; P = 0·008) and Enterobacter cloacae (0 versus 20·4 per cent; P = 0·033). This shift was associated with a high incidence of bacterial resistance against ampicillin–sulbactam (63·6 per cent versus 18 per cent in patients with no PBD; P < 0·001), piperacillin–tazobactam (30·1 versus 0 per cent respectively; P = 0·003), ciprofloxacin (28·5 versus 5 per cent; P = 0·047) and imipenem (26·6 versus 0 per cent; P = 0·011). The rate of wound infection was higher in patients with a positive bile culture (21·0 per cent versus 6 per cent in patients with sterile bile; P = 0·002). Regression analysis revealed the presence of Enterococcus faecium (odds ratio 2·83, 95 per cent c.i. 1·17 to 6·84; P = 0·021) and Citrobacter species (odds ratio 5·09, 1·65 to 15·71; P = 0·005) as independent risk factors for postoperative wound infection. Conclusion: There are fundamental differences in the biliary microbiome of patients with periampullary cancer who undergo PBD and those who do not. PBD induces a shift of the biliary microbiome towards a more aggressive and resistant spectrum, which requires a differentiated perioperative antibiotic treatment strategy. Abstract : More resistant bacteria